Comparing cardiac radiation dose between accelerated partial breast irradiation and whole breast irradiation: A narrative review - Alexis N. Reinders; Eilidh M. O’Brien; Gregory Mark Hermann (Annals of Oncology Research and Therapy, 2025)
Breast-conserving surgery with whole breast irradiation (WBI) is the standard of care for early-stage breast cancer which provides similar local control and survival outcomes to mastectomy alone. Advances in radiation therapy (RT), such as hypofractionated RT and accelerated partial breast irradiation (APBI), have demonstrated equivalent cancer control with the benefit of lower cardiac exposure. We conducted a comprehensive literature search from May 2024 to July 2024, focusing on search terms related to breast irradiation and cardiac toxicity. We reviewed and included 34 articles on cardiac dosing (i.e., mean heart dose and left anterior descending (LAD) coronary artery dose). The purpose of our study was to review the current literature on cardiac dosing in breast cancer patients with a focus on comparing the cardiac toxicity of WBI versus APBI. APBI is noninferior to WBI with regard to local recurrence, although APBI techniques differ in their efficacy. Notably, most APBI techniques display superiority with regard to reducing cardiac toxicity. Additional studies are needed to compare cardiac toxicity between APBI techniques and the long-term effects of APBI versus WBI. In conclusion, compared to WBI, APBI provides notable benefits, such as reduced heart radiation exposure and long-term coronary event risks while offering a more convenient and accessible treatment schedule.